Performance and Emissions Analysis of BE85-Gasoline Blends on Spark Ignition Engine - Hendry Y. Nanlohy; Helen Riupassa; Marthina Mini; Herman Tjolleng Taba; Basri Katjo; Nevada JM Nanulaitta; Masaki Yamaguchi (Universitas Muhammadiyah Magelang, 2022)
This study aims to reveal the performance and exhaust emissions of a spark ignition (SI) engine fueled by a gasoline-bioethanol mixture. The main performance characteristics of the SI engine tested are torque, power output; thermal efficiency, brake specific fuel consumption, and brake mean effective pressure. Meanwhile, the exhaust emissions seen are carbon monoxide and hydrocarbons. The test is carried out by comparing the performance of the SI engine under standard conditions without modification with gasoline fuel, with the SI engine with modification with 85% bioethanol fuel. The mass flow of fuel is regulated by modifying the carburetor choke at 3/4 and 7/8. The results show that although slightly lower than gasoline, in general, it can be seen that bioethanol can improve SI engine performance and produce environmentally friendly exhaust emissions.